Calprotectin Is a Useful Tool in Distinguishing Coexisting Irritable Bowel-Like Symptoms from That of Occult Inflammation among Inflammatory Bowel Disease Patients in Remission - Jelsness-Jørgensen, Lars-Petter (Hindawi Publishing Corporation, 2013)
Background and Aim. In the inflammatory bowel diseases (IBDs), many symptoms are similar to the functional disorder irritable bowel syndrome (IBS). A challenge is thus to distinguish symptoms of IBD from IBS. The aim of this study was to investigate the levels of calprotectin in IBS-positive IBD patients in remission. Methods. Remission was defined as a simple clinical colitis activity index (SCCAI) or simple crohn's disease activity index (SCDAI) score of less than three and less than four, respectively. The Rome II criteria were used to identify cases, and the calprotectin ELISA test was used to quantify calprotectin in stools. Results. The Rome II criteria were fulfilled in 24.6% of ulcerative colitis (UC) patients, while the comparable number for Crohn's disease (CD) was 21.4%. There was a tendency for elevated fecal calprotectin levels in IBS-positive patients, regardless of diagnosis. However, these differences were only significant in CD. Conclusions. Calprotectin levels are elevated in subgroups of IBD patients that are in remission and have coexisting IBS-like symptoms. This study underscores the clinical usefulness of a noninvasive marker to distinguish patients in need of intensified followup from those that do not need further workup.